Obstetric Health Care Providers' Counseling Responses to Pregnant Patient Disclosures of Marijuana Use. Issue 4 (April 2016) - Holland, Cynthia L.; Rubio, Doris; Rodriguez, Keri L.; Kraemer, Kevin L.; Day, Nancy; Arnold, Robert M.; Tarr, Jill A.; Chang, Judy C.
Abstract : OBJECTIVE: To describe obstetric health care providers' responses and counseling approaches to patients' disclosures of marijuana use during first prenatal visits. METHODS: We performed a content analysis of audio-recorded patient–health care provider first prenatal visits for obstetrics health care providers' responses to patients' disclosure of marijuana use. The study was conducted at five urban outpatient clinics located in Pittsburgh, Pennsylvania. RESULTS: Among 468 audio-recorded first obstetric encounters, 90 patients (19%) disclosed marijuana use to 47 health care providers; mean number of recoded encounters containing marijuana disclosures for participating health providers was 1.8±1.4. In 48% of these 90 visits, obstetric health care providers did not respond to marijuana use disclosures or offer counseling. When counseling was offered, it consisted of general statements without specific information on the risks or outcomes related to marijuana use in pregnancy, discussions regarding the need for urine toxicology testing, and warnings that use detected at the time of delivery would initiate child protective services involvement. CONCLUSION: Obstetric health care provider responses to disclosure of marijuana use occurred in approximately half of patient encounters when marijuana use was disclosed and focused on legal and procedural consequences with less focus on health or medical implications. Our results suggest a need for health care provider training on potential consequences of perinatal marijuana use and communication skills for counseling patients about perinatal marijuana. Abstract : Direct observation of audio-recorded first prenatal visits show health care providers do not counsel patients on medical risks and potential negative outcomes of marijuana use during pregnancy.